Management of Food-Related Diarrhea Outbreak in the Emergency Department: Lessons Learned from the German STEC O104:H4 Epidemic. (11th October 2015) - Sayk, Friedhelm; Asselborn, Niels Henrik; Eisemann, Nora; Katalinic, Alexander; Metzner, Jörg; Wolfrum, Sebastian; Fellermann, Klaus; Knobloch, Johannes; Nitschke, Martin
Abstract : Emergency department (ED) management of the German STEC O104:H4 outbreak in 2011 was not limited to patients being truly infected with STEC. In parallel to spread of alarming news in public media, patients suffering from diarrhea due to other reasons fearfully presented, equally. We retrospectively characterized these two cohorts for anamnestic, clinical, and laboratory findings at their first ED contact. From 15th of May to July 2011, 302 adult patients with diarrheal complaint presented at the EDs of two tertiary hospitals in Lubeck, northern Germany. Fecal testing for STEC was obtained in 245 (81%) patients: 105 were STEC-positive and 140 were STEC-negative. Anamnestic characteristics (defecation rate, visible bloody diarrhea, and lower abdominal pain), abdominal tenderness, and some laboratory findings were significantly different between both cohorts but not reliable to exclude STEC. In >90% of STEC-positive patients diarrheal symptoms had started in May, reflecting the retrospective nationwide peak of infections, whereas the majority of STEC-negative patients became symptomatic in June 2011. During the German STEC O104:H4 outbreak a definite distinction at initial ED contact between STEC-positive versus STEC-negative patients by clinical judgment alone was not reliable. Fecal testing in the ED, however, might survey the outbreak of foodborne infections with the utmost precision.